The Relationship Between Nasal Septal Deviation, Daytime Sleepiness and School Performance Among Iranian High School Students: A Pilot Cross-Sectional Study - Mahbubeh Ebrahimnegad Shirvani; Sirous Tayebi; Patricia Khashayar; Ata Pourabbasi (Shiraz University of Medical Sciences, 2015)
Background: The most important factors affecting students' learning ability are attention and concentration, which are impaired by daytime sleepiness in classroom. Objectives: This study was conducted to determine the effect of nasal septal deviation on daytime sleepiness and school performance among high school students. Patients and Methods: This study comprised 172 high school male students, who were examined for septal deviation by a practitioner. Daytime sleepiness was determined by school consultants. Grade point average (GPA) was considered as an index for school performance. Results: Nasal septal deviation was significantly more prevalent among sleepy students (46.8%) compared to their attentive peers (22.8%, P < 0.05). Although the GPAs in students with septal nasal deviation were lower than other students, the difference was not statistically significant. Conclusions: It is not unlikely that nasal cavity deformities such as septal deviation that results in sleep disturbances would lead to poor school performance in students. However, the question to be answered is whether deviated nasal septum is the only cause of poor performance of students or it involves some other mechanisms. Further studies are needed to confirm this relationship and whether reconstruction of structural anomalies of the nasal cavity in students prevents daytime sleepiness and subsequently improves their school performance.